Gonadal Y-chromosome mosaicism with 45, X Turner syndrome complicated with bilateral HCG-secreting gonadoblastoma - Zheng, Rujiang; Chen, Qiuli; Ma, Huamei; Liu, Juncheng; Chen, Huadong; Liang, Jianbo; Chen, Hongshan; Zhang, Jun; Li, Yanhong; Guo, Song; Wang, Bing; Du, Minlian (Frontiers in Pediatrics, 2022)
We report a rare case of bilateral HCG-secreting gonadoblastomas (Gb) in a 5.25-year-old girl of 45, X Turner syndrome (TS) with gonadal Y chromosome mosaicism. The clinical data were summarized, and the literatures were reviewed. The patient had enlarged breasts for 2 years and 3 months, with elevated β-HCG of blood found for 8 months. The level of β-HCG of cerebrospinal fluid, cranial MRI, chest and abdominal CT, and pelvic MRI were normal. After surgical gonad exploration, biopsy and excision, gonad venous blood hormone examination and SRY gene detection of gonad tissue, the diagnosis was confirmed as HCG-secreting Gb (bilateral) and TS (45, X) with gonad Y chromosome mosaicism. The patient received 4 courses of chemotherapy, and regular outpatient follow-up. At 9 months after gonadectomy, there was no clinical, laboratory, or radiological evidence of recurrence. We reported a nonclassical case of 45, X Turner syndrome (TS) with gonadal Y chromosome mosaicism, who presented with breast development as the first manifestation and then virilization due to bilateral HCG-secreting gonadoblastomas. Detection of serum β-HCG and AFP is requisite for the diagnosis of precocious puberty, karyotyping is important for virilizing phenotypic female, and virilization in Turner syndrome implies the existence of Y chromosome(substance) (peripheral blood or tissue mosaicism) and the occurrence of gonadal tumors.